EFFECT OF PRE-OPERATIVE NUTRITIONAL DEFICIENCY ON MORTALITY AFTER RADICAL CYSTECTOMY FOR BLADDER CANCER - Gregg, Justin R. (2010)
INTRODUCTION AND OBJECTIVES: Poor preoperative nutritional status is a risk factor for adverse outcomes after major surgery. We evaluated the effect of preoperative nutritional deficiency (ND) on peri–operative mortality and overall survival in patients undergoing radical cystectomy (RC) for bladder cancer. METHODS: 538 patients underwent RC for urothelial carcinoma (UC) between January 2000 and June 2008 and had nutritional parameters documented. Patients with preoperative albumin <3.5 g/dL, BMI <18.5 or pre–surgical weight loss >5% of body weight were considered ND. Primary outcomes were 90–day mortality and overall survival. Survival was estimated using Kaplan–Meier analysis and compared using the log–rank test. Cox proportion hazards models were used for multivariate survival analysis. RESULTS: 103 of 538 patients (19%) met criteria for ND. 90–day mortality was 7.3% overall (39 deaths); 16.5% in patients with ND and 5.1% in the others, p<0.01..ND was a strong predictor of death within 90 days on multivariate analysis (HR 2.91, 95% CI [1.36, 6.23], p<0.01). Overall survival at 3 years was 44.5% (33.5, 54.9) for ND patients and 67.6% (62.4, 72.2) for nutritionally normal patients, p<0.01. On multivariate analysis, ND patients had significantly higher risk of all-cause mortality (HR 1.82, 95% CI [1.25, 2.65], p<0.01). CONCLUSIONS: Nutritional deficiency, as measured by preoperative weight loss, BMI and serum albumin, is a strong predictor of 90–day mortality and poor overall survival. Prospective studies are needed to demonstrate the best indices of preoperative nutritional status and whether nutritional intervention can alter the poor prognosis for RC patients with nutritional deficiencies.